2018
DOI: 10.1002/jcb.27867
|View full text |Cite
|
Sign up to set email alerts
|

RSPO2 enhances cell invasion and migration via the WNT/β‐catenin pathway in human gastric cancer

Abstract: R‐spondins comprise a group of secreted WNT agonists. R‐spondin2 (RSPO2) plays a crucial role in the activation of the WNT/β‐catenin pathway and oncogenesis, though its specific role in human gastric cancer (GC) remains unclear. In the current study, RSPO2 expression levels were upregulated in cancer specimens and cell lines (AGS and BGC‐823). Inhibition of RSPO2 expression levels had distinct effects on cell invasion, migration, and epithelial‐mesenchymal transition (EMT) in AGS and BGC‐823 cells in vitro. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…The study also represents an important advance in understanding the molecular mechanism behind the role of the Rspo2-LGR4 system in TSCC progression, as the authors investigated the signalling pathways underlying this system. Supported by previous publications, the authors were able to prove that the Rspo2-LGR4 system works through the Wnt/β-catenin signalling pathway [7,8].…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The study also represents an important advance in understanding the molecular mechanism behind the role of the Rspo2-LGR4 system in TSCC progression, as the authors investigated the signalling pathways underlying this system. Supported by previous publications, the authors were able to prove that the Rspo2-LGR4 system works through the Wnt/β-catenin signalling pathway [7,8].…”
mentioning
confidence: 73%
“…In EBioMedicine , Zhang et al studied the role of the R-spondin 2-LGR4 system in tongue (T) SCC as an example of SCC both in general, and HNSCC specifically [9]. Studying this system in TSCC is of profound importance mainly because 1) the R-spondin 2-LGR4 system had not been studied before in TSCC, and 2) there are conflicting results about its role in other solid cancers, such as colon, breast, and gastric cancer ([2,4,6,8,10]. The role of R-spondin 2 in colon cancer represents a clear example of these contradictory results, as it was reported to enhance cancer progression by enriching LGR5 + stem cells; but at the same time supress cancer progression through inhibiting Wnt/β-Catenin signalling leading to a reduction in cancer cell proliferation and metastases formation [4,6,10].…”
mentioning
confidence: 99%
“…High expression of LGR5 and EMT was reported to be correlated in gastric cancer [13]. Furthermore, Zhang et al reported that RSPO2, a ligand of LGR5, promotes EMT in gastric cancer cells by activating WNT/β-catenin signaling via LGR5 [14]. Therefore, elucidation of the relationship between LGR5 and RSPO2 in PD-AC may lead to the development of new therapeutic methods and an improved prognosis for PD-AC.…”
Section: Discussionmentioning
confidence: 99%
“…High LGR5 expression and EMT were reported to be correlated in gastric cancer [15]. Furthermore, Zhang et al reported that the LGR5 ligand RSPO2 promotes EMT in gastric cancer cells by activating WNT/β-catenin signaling via LGR5 [16]. Therefore, elucidation of the relationship between LGR5 and RSPO2 in PD-AC may lead to the development of new therapeutic methods and an improved prognosis for PD-AC.…”
Section: Discussionmentioning
confidence: 99%